Analysis of floor price trend of raw coffee in Nepal - Luitel, G.; Acharya, B. (Journal of Agriculture and Forestry University, 2022)
Nepalese coffee industry has passed a long way of production, processing and marketing. Coffee as a high value crop with floor price helped farmers to sustain their production. This study reviews the historic approaches of floor price fixation system and its trend using secondary data of National Tea and Coffee Development Board (NTCDB). The floor prices were averaged and converted into Green Bean Equivalent (GBE) units and analysed in different time zones. It was found that the floor price fixation system has been changing over years. The floor price was roughly based on transportation cost in earlier years. Grading-based price fixation of fresh cherry came into practice during 2002/03-2005/06. Eventually, more precise and practicable floor price measures were introduced for different quality grades, which was practiced for almost a decade from 2006/07 to 2014/15. Starting from 2015/16, previous approach was slightly modified based on organic certification which is still in practice. Moreover, it was found that the price of raw coffee has increased notably over years. While the price index of raw coffee in 1994/95 was merely 26.37, it has increased by more than nine times to 243.12 in 2021/22. Since higher priced raw coffee will not make it competitive in the global market, the floor price should be adjusted based on international market trend, considering macroeconomic parameters as well.